From Servicescape to Loyalty: How Muslim and Non-Muslim Customers Experience Islamic Banking through Strategic Experiential Modules (SEMs) - Dakwah, M. Mujahid; Faidal, Faidal; Roodhi, Mohammad Najib (Program Studi Perbankan Syariah, IAIN Palopo, 2025)
The growth of Islamic banking has continued steadily in Indonesia and globally, yet maintaining customer loyalty remains a persistent challenge amid increasing competition from conventional banks and fintech services. This study examines the mediating role of Strategic Experiential Modules (SEMs) in the relationship between servicescape elements such as ambient conditions, layout design, and signs and symbolic design, and customer satisfaction and loyalty in Islamic banking. Employing a comparative and explanatory approach, data were collected from 397 Muslim and non-Muslim customers of Islamic banks in Indonesia using purposive sampling, then analyzed using Partial Least Squares Structural Equation Modeling (PLS SEM). The results indicate that layout and symbolic design significantly influence SEMs, which in turn have a strong positive effect on customer satisfaction and loyalty. Satisfaction also acts as a significant predictor of loyalty. Notably, the SEMs framework proved effective across religious segments, affirming its relevance in both value driven and inclusive service contexts. The study underscores the need for Islamic banks to enhance physical design, symbolic cues, and emotional engagement to deliver more holistic and meaningful service experiences. These findings suggest that integrating experiential strategies with inclusive service principles is essential for building long term customer relationships in Islamic banking.